PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR IPS MURID KELAS IV SD INPRES BARRANG CADDI II KOTA MAKASSAR - Jumrah, Abrina Maulidnawati (Fakultas Keguruan dan Ilmu Penidikan UIM, 2019)
Abstract: The Application of Cooperative Learning Model Type Teams Games Tournament (TGT) to Improve Social Studies Learning Outcomes of Students in Class IV SD Inpres Barrang Caddi II Makassar. The purpose of this study was to improve social studies learning outcomes by implementing cooperative learning types of teams games tournament (TGT) in fourth grade students of SD Inpres Barrang Caddi II Makassar. The approach used in this research was a qualitative approach and the type of research was Classroom Action Research (CAR). The focus on this classroom research was: 1. Teacher, namely how teachers plan learning steps to be achieved to maximum 2. Students, namely to improve student learning outcomes in social science subjects ( IPS) through the cooperative approach of Teams Games Tournament (TGT) model IV SD Inpres Barrang Caddi II Makassar. Data collection techniques were observation and learning achievement tests. Learning outcomes of social science (IPS) grade IV students of SD Inpres Barrang Caddi II in Makassar City had improved after the two teams learning tournament (TGT) held for two cycles. Improved learning outcomes were shown by an increase of evaluation test results in each cycle. In the first cycle the average score reached 63.33, and the second cycle increased to 70.37. While the classical completeness of cycle I, which was 44.44%, had not met the indicators of success. But in the second cycle classical completeness increased to 85.18% and had met the indicators of success.Keywords: Student Learning Outcomes, Teams Games Tournament Model (TGT).